Correlation between ECG and Heart Sound - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2020)
In addition to electrical signals from the heart, signals related to heart sound can be received. Electrocardiogram (ECG) data are electrical signals that result in activities in the heart muscles. Phonocardiogram data are the results of turbulence during the opening and closing of the heart valves. In this paper, electrical signals (ECG) and sound signals (FCG) are taken from a healthy heart and the relation of two signals is defined. By defining the relation of two signals, it's aimed to establish the ground for the algorithms to be arranged in the future. © 2020 IEEE.
Keywords: Cross-Correlation; Electrocardiogram; Heart; Heart Sound; Phonocardiogram